2014
DOI: 10.1007/s11538-014-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the Transmission of Infection in the Spread of Epidemics: Interacting Random Walkers with and Without Confinement

Abstract: A theory of the spread of epidemics is formulated on the basis of pairwise interactions in a dilute system of random walkers (infected and susceptible animals) moving in n dimensions. The motion of an animal pair is taken to obey a Smoluchowski equation in 2n-dimensional space that combines diffusion with confinement of each animal to its particular home range. An additional (reaction) term that comes into play when the animals are in close proximity describes the process of infection. Analytic solutions are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 37 publications
(38 reference statements)
1
31
0
Order By: Relevance
“…Though we do not propose that our formalism is necessarily applicable to the study of motion of excitations in doped molecular crystals, the quantum yield style calculations outlined above have found recent use in other systems. For example, in the context of Smoluchowski random walkers [23] and in the transmission of infectious epidemics [24], it was demonstrated that the interplay between diffusion, confinement and absorption at site x may bring about non-monotonic dependencies of the quantum yield. We explore below such non-monotonic dependencies in our formalism.…”
Section: Traps Impartial Detection and Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Though we do not propose that our formalism is necessarily applicable to the study of motion of excitations in doped molecular crystals, the quantum yield style calculations outlined above have found recent use in other systems. For example, in the context of Smoluchowski random walkers [23] and in the transmission of infectious epidemics [24], it was demonstrated that the interplay between diffusion, confinement and absorption at site x may bring about non-monotonic dependencies of the quantum yield. We explore below such non-monotonic dependencies in our formalism.…”
Section: Traps Impartial Detection and Yieldmentioning
confidence: 99%
“…In the absence of traps or guest molecule and the associated probability decay, that is respectively with C e → 0 and τ e → +∞ or C → 0 and τ → +∞, the form of the propagator reduces to the one found in Eq. (24).…”
Section: Appendix Amentioning
confidence: 99%
“…V.M. Kenkre et al have studied the effect of confinement on the spread of epidemics in a system of random walkers who move in n dimensions [56]. They have found that the spread of the epidemic has a nonmonotonic dependence on the extent of the home range of the individuals.…”
Section: Introductionmentioning
confidence: 99%
“…We present below analysis and practically usable results for random walkers moving under a confinement potential and interacting when they arrive within the influence of one another. We develop the theory as an extension of work we have published recently [3] where we have provided a general formalism and illustrated it explicitly for a specific 1-dimensional case. The application in mind here, as in ref.…”
mentioning
confidence: 99%
“…The application in mind here, as in ref. [3], is to the description of transmission of epidemics such as the Hantavirus [4], wherein rodents moving randomly on the terrain pass on infection on encounter.…”
mentioning
confidence: 99%